IMPACT OF DEVELOPMENT EXCHANGE CENTRE (DEC) MICROCREDIT PROGRAMME ON CROP OUTPUT AND STANDARD OF LIVING AMONG WOMEN FARMERS IN KADUNA STATE, NIGERIA - Adamu, B. D.; Michael , H. Y. (FUDMA JOURNAL OF SCIENCES, 2021)
This study examined the impact of Development Exchange Centre microcredit programme on crops output and standard of living among women farmers in Kaduna State, Nigeria. A multi-stage sampling method was employed to select 420 respondents. Primary data were collected through the use of questionnaires and were subjected to both descriptive and inferential statistics. The mean farming experience was 22 years for DEC participants and 19 years for non-DEC participants while mean farm size for participants and non-DEC participants was 2.0 ha. Determinant of standard of living on programme participants, the study concludes that, age (0.0405, P<0.01), farm size (47.510, P<0.01), education, credit (0.6031, P< 0.01) and extension contact (0.002, P< 0.01), had direct relationship with the standard of living of programme participants, This implies DEC, increase the standard of living of programme participants in Kaduna State. Determinant of crops output of programme participants shows that, farm size (0.046, P<0.01), credit (0.821, P< 0.01), extension contact (0.0542, P< 0.05). F-chow statistics shows that DEC microcredit had positive impact on crops output of programme participants. Z – statistics also indicated positive impact on living standard of the participants. It was recommended that, DEC microcredit organization should increase the amount of loan disbursement to N100, 000, so as to increase participation; extend the repayment period, lowered interest rates and extend the programme to other farming communities in Kaduna State, there by improving the standard of living of women farmers in the state